PERSPECTIVE OF LITERATURE TOURISM DEVELOPMENT UNDER THE SHADOWS OF CORONA LITERATURE - Suwardi Edraswara (Prosiding Seminar Nasional dan Internasional HISKI, 2020)
The perspective of developing literary tourism is currently overshadowed by the corona. Since Covid-19 has spread, literary tourism needs a special strategy. The perspective of developing literary tourism certainly requires a unique strategy. In this connection, this article attempts to describe four perspectives of developing literary tourism as an alternative route.First, literary ethnobotany tourism is always contextual, following the flow of the times as the development of literary tourism. Nevertheless, with the spread of corona literature, it has impacted the bargaining power of literary ethnobotany tourism. Ethnobotany tourism will use local plants as a mainstay of literary tourism. Second, literary sports tourism is a perspective of understanding and developing literature based on tourism and sports. The focus of this perspective remains on literature. Third, the perspective of literary spice tourism is the perspective of understanding and developing functional literary lines. Literature turns out to be able to adapt and contribute to literary tourism and at the same time, make it healthy. Fourth, the literary iconology tourism perspective is a literary development perspective related to literary inspiration sources.